Textbook of Head and Neck Pathology Volume 2: Mouth, Oropharynx, and Larynx - Brandwein-Weber, Margaret S. (Springer International Publishing, 2018)
The second of a four-volume set, this book covers oral cavity and oropharynx pathology. It's goal is to become a "go-to" sign-out resource for head and neck pathology, incorporating anatomy, staging, diagnostic, and prognostic information. This richly illustrated volume has a bullet point format, where appropriate, allowing information to be easily located. This book is aimed at trainee and practicing pathologists in the USA and worldwide, and is also of interest to oral pathologists and oral pathology trainees.